Normativna koncepcija historije političke misli / Normative Concept of Political Thought's History: Zgodićeva vizija Bosne i bošnjačkog identiteta / Zgodić's Vision of Bosnia and Herzegovina Identity - Fejzić, Elvis (Pregled: časopis za društvena pitanja / Periodical for social issues, 2020)
The Text deals with Normative Concept of Political Thought's History : Zgodić's Vision of Bosnia and Herzegovina Identity.